Profitabilitas dan Ukuran KAP Terhadap Audit Delay pada Perusahaan Barang Konsumen Non Primer yang Terdaftar di DES Tahun 2021-2024 - Enandar, Azizah Haura; Gojali, Dudang; Yulianti, Lina (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025)DO - 10.51211/joia.v10i1.3480, 2025)
The purpose of this study was to investigate the relationship between audit delay and Public Accounting Firm (PAF) size and profitability in non-primary consumer goods businesses listed on the Sharia Securities List between 2021 and 2024. Thirty-two non-primary consumer products firms satisfied the sample requirements based on the purposive sampling approach. The Indonesia Stock Exchange's official website (www.idx.co.id) provided the financial statement data. The study's findings demonstrated that, when evaluated partially, the profitability variable significantly reduced audit delay, while the PAF size variable had no discernible partial impact on audit delay. Additionally, audit delay was significantly impacted by both PAF size and profitability at the same time. .   Keywords : Profitability, Size of Public Accounting Firm, Audit Delay